Flachheitsbasierte Methode zum stoßfreien Umschalten von Reglerstrukturen - Osmic, Semir

Ground State Connectivity of Local Hamiltonians - Gharibian, Sevag; Sikora, Jamie (International Colloquium on Automata, Languages, and Programming (ICALP 2015))
The study of ground state energies of local Hamiltonians has played a fundamental role in quantum complexity theory. In this paper, we take a new direction by introducing the physically motivated notion of ``ground state connectivity'' of local Hamiltonians, which captures problems in areas ranging from quantum stabilizer codes to quantum memories. We show that determining how ``connected'' the ground space of a local Hamiltonian is can range from QCMA-complete to PSPACE-complete, as well as NEXP-complete for an appropriately defined ``succinct'' version of the problem. As a result, we obtain a natural QCMA-complete problem, a goal which has generally proven difficult since the conception of QCMA over a decade ago. Our proofs rely on a new technical tool, the Traversal Lemma, which analyzes the Hilbert space a local unitary evolution must traverse under certain conditions. We show that this lemma is essentially tight with respect to the length of the unitary evolution in question.

Quantum Hamiltonian Complexity - Gharibian, Sevag; Huang, Yichen; Landau, Zeph; Woo Shin, Seung (Foundations and Trends® in Theoretical Computer Science)
Constraint satisfaction problems are a central pillar of modern computational complexity theory. This survey provides an introduction to the rapidly growing field of Quantum Hamiltonian Complexity, which includes the study of quantum constraint satisfaction problems. Over the past decade and a half, this field has witnessed fundamental breakthroughs, ranging from the establishment of a “Quantum Cook-Levin Theorem” to deep insights into the structure of 1D low-temperature quantum systems via so-called area laws. Our aim here is to provide a computer science-oriented introduction to the subject in order to help bridge the language barrier between computer scientists and physicists in the field. As such, we include the following in this survey: (1) The motivations and history of the field, (2) a glossary of condensed matter physics terms explained in computer-science friendly language, (3) overviews of central ideas from condensed matter physics, such as indistinguishable particles, mean field theory, tensor networks, and area laws, and (4) brief expositions of selected computer science-based results in the area. For example, as part of the latter, we provide a novel information theoretic presentation of Bravyi’s polynomial time algorithm for Quantum 2-SAT.

Tensor network non-zero testing - Gharibian, Sevag; Landau, Zeph; Woo Shin, Seung; Wang, Guoming (Quantum Information & Computation)
Tensor networks are a central tool in condensed matter physics. In this paper, we initiate the study of tensor network non-zero testing (TNZ): Given a tensor network T, does T represent a non-zero vector? We show that TNZ is not in the Polynomial-Time Hierarchy unless the hierarchy collapses. We next show (among other results) that the special cases of TNZ on non-negative and injective tensor networks are in NP. Using this, we make a simple observation: The commuting variant of the MA-complete stoquastic k-SAT problem on D-dimensional qudits is in NP for logarithmic k and constant D. This reveals the first class of quantum Hamiltonians whose commuting variant is known to be in NP for all (1) logarithmic k, (2) constant D, and (3) for arbitrary interaction graphs.

Internet, Kapitalismus und periphere Entwicklung im Waldviertel - Fuchs, Christian (Momentum Quarterly – Zeitschrift für sozialen Fortschritt (Journal for Societal Progress))

Internet, Capitalism, and Peripheral Development in the Waldviertel - Fuchs, Christian (New Proposals)

Martin-Heidegger’s anti-Semitism: Philosophy of Technology and the Media in the Light of the “Black Notebooks“. Implications for the Reception of Heidegger in Media and Communication Studies - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Left-Wing Media Politics and the Advertising Tax. Reflections on Astra Taylor’s Nook “The People’s Platform: Taking Back Power and Culture in the Digital Age“ - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Surveillance and Critical Theory. In Surveillance: Critical Analysis and Current Challenges: Special issue edited by James Schwoch, John Laprise and Ivory Mills - Fuchs, Christian (Media and Communication)

Digital Labour: A Comment on César Bolaño’s tripleC Reflection - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Antisemitismo e tecnofobia: il quarto volume dei Quaderni neri di Martin Heidegger (1942-1948) - Fuchs, Christian (Kasparhauser, September 15, 2015)

The Internet, Freedom, and Ideology in the Age of Mass Surveillance - Fuchs, Christian (The Opticon – A Newspaper on Privacy and Surveillance)

Trabajadores Digitales del mundo, uníos! Un marco para teorizar críticamente y analizar el trabajo digital - Fuchs, Christian; Sandoval, Marisol (Revista Hipertextos: Capitalismo, Técnica y Sociedad en debate)

Trabalhadores digitais do mundo inteiro uni-vos: teorizando e analisando criticamente o trabalho digital - Fuchs, Christian; Sandoval, Marisol (Parágrafo: Revista Científica de Comunicação Social da FIAM-FAAM)

Mídias Sociais e a Esfera Pública - Fuchs, Christian (Revista Contracampo)

Anti-Semitism, Anti-Marxism, and Technophobia: The Fourth Volume of Martin Heidegger’s Black Notebooks (1942-1948) - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Reflections on Todd Wolfson’s Book “Digital Rebellion: The Birth of the Cyber Left” - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Surface-modified CAU-10 MOF materials as humidity sensors: impedance spectroscopic study on water uptake - Weiss, Alexander; Reimer, Nele; Stock, Norbert; Tiemann, Michael; Wagner, Thorsten (Physical Chemistry Chemical Physics)
Metal–organic frameworks (MOFs) are crystalline microporous materials with tunable chemical and physical properties. By combining various metal clusters with different interconnecting organic linkers, the pore structure, crystallinity, as well as the surface properties can be modified. In the present work, modification of the organic linker molecules is utilized to synthesize CAU-10 type MOFs with variable affinity of the pore surface to water. In principle, this should influence the accessibility of the pores for water vapor and therefore offer a tool to control its sorption properties. For a deeper understanding we studied the water sorption characteristics and compared the results to the conductive and dielectric properties studied by impedance spectroscopy. Spectra in a wide frequency range from 1 mHz to 1 MHz were recorded. Data analysis is performed using the Havriliak–Negami model. The MOFs are also tested as sensitive layers for capacitive humidity sensing by correlating the change in permittivity of the materials with the amount of physisorbed water. Such an MOF-based sensor was tested with respect to environmental monitoring and compared to a commonly used commercial humidity sensor.

Synthesis of Mesoporous Metal Oxides by Structure Replication: Thermal Analysis of Metal Nitrates in Porous Carbon Matrices - Weinberger, Christian; Roggenbuck, Jan; Hanss, Jan; Tiemann, Michael (Nanomaterials)
A variety of metal nitrates were filled into the pores of an ordered mesoporous CMK-3 carbon matrix by solution-based impregnation. Thermal conversion of the metal nitrates into the respective metal oxides, and subsequent removal of the carbon matrix by thermal combustion, provides a versatile means to prepare mesoporous metal oxides (so-called nanocasting). This study aims to monitor the thermally induced processes by thermogravimetric analysis (TGA), coupled with mass ion detection (MS). The highly dispersed metal nitrates in the pores of the carbon matrix tend to react to the respective metal oxides at lower temperature than reported in the literature for pure, i.e., carbon-free, metal nitrates. The subsequent thermal combustion of the CMK-3 carbon matrix also occurs at lower temperature, which is explained by a catalytic effect of the metal oxides present in the pores. This catalytic effect is particularly strong for oxides of redox active metals, such as transition group VII and VIII metals (Mn, Fe, Co, Ni), Cu, and Ce.

How Smart Is “Smart Security”? Exploring Data Subjectivity and Resistance. Final Report - Baur-Ahrens, Andreas; Krüger, Marco; Ammicht Quinn, Regina; Leese, Matthias; Matzner, Tobias